POLA KOMUNIKASI ORANG TUA DALAM INTERVENSI PERKEMBANGAN BAHASA PADA ANAK DENGAN GANGGUAN TERLAMBAT BICARA (SPEECH DELAY) (STUDI KASUS ZH) PARENT COMMUNICATION PATTERNS IN THE INTERVENTION OF LANGUAGE DEVELOPMENT IN SPEECH DELAY CHILDREN (CASE STUDY OF ZH) - Jennyfer Puji Lestari Woi; Syahrul Ramdhan; Erizal Gani (Metalingua: Jurnal Penelitian Bahasa, 2021)
Children can experience a disorder in their communication which is called speech delay. Speech delay is a condition when a child has difficulty in expressing his feelings or desires to other people. This difficulty is shown in inability to communicate or speak clearly. This article discusses the case of a child named ZH who experienced speech delays reaching the age of five year old. This is a case study research with qualitative approach. The data were collected by recording and writing, and then were analyzed by data reduction technique.  The authors drew final conclusions based on the data obtained and supported by theoretical studies. The results showed that parental communication patterns greatly influence language development in children. In this case, the communication pattern of parents towards ZH refers to the Tan-Soederbergh and Xavier Tan methods. This has resulted in many significant advances for language development in ZH. At the age of five, ZH has started to use vocabulary a lot to ask questions and explain things.